DAS28-CRP and DAS28-ESR cut-offs for high disease activity in rheumatoid arthritis are not interchangeable. Issue 1 (30th January 2017) - Fleischmann, Roy M; van der Heijde, Désirée; Gardiner, Philip V; Szumski, Annette; Marshall, Lisa; Bananis, Eustratios
Abstract : Background: In most patients with rheumatoid arthritis (RA), Disease Activity Score 28-joint count C reactive protein (DAS28-CRP) is lower than DAS28 erythrocyte sedimentation rate (DAS28-ESR), suggesting that use of the DAS28-ESR cut-off to assess high disease activity (HDA) with DAS28-CRP may underestimate the number of patients with HDA. We determined the DAS28-CRP value corresponding to the validated DAS28-ESR cut-off for HDA. Methods: Baseline data were pooled from 2 clinical studies evaluating etanercept (ETN) plus methotrexate (MTX) or MTX in early RA; DAS28-CRP and DAS28-ESR were obtained, allowing the determination of the DAS28-CRP HDA value best corresponding to the DAS28-ESR cut-off of >5.1. Results: At baseline, as expected, fewer patients had HDA by DAS28-CRP than DAS28-ESR; DAS28-CRP>5.1 and DAS28-ESR>5.1 had only modest agreement (κ coefficients 0.45–0.54). Mean DAS28-CRP and DAS28-ESR were 5.7 and 6.2, respectively, in the ETN+MTX group (n=571), and 6.0 and 6.5 in the MTX group (n=262). A DAS28-CRP cut-off of 4.6 corresponded to a DAS28-ESR cut-off of 5.1. Conclusions: We have shown that a DAS28-CRP of 4.6 corresponds to 5.1 for DAS28-ESR. Since this is substantially lower than the DAS28-ESR cut-off of 5.1, using 5.1 as the cut-off for DAS28-CRP underestimates disease activity in RA. Trial registration number: NCT00195494 ; NCT00913458 .